1999
DOI: 10.1038/sj.ejcn.1600692
|View full text |Cite
|
Sign up to set email alerts
|

Intake of fatty acids in Western Europe with emphasis on trans fatty acids: The TRANSFAIR study

Abstract: Objective: To assess the intake of trans fatty acids (TFA) and other fatty acids in 14 Western European countries. Design and subjects: A maximum of 100 foods per country were sampled and centrally analysed. Each country calculated the intake of individual trans and other fatty acids, clusters of fatty acids and total fat in adults andaor the total population using the best available national food consumption data set. Results: A wide variation was observed in the intake of total fat and (clusters) of fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
3
20

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(273 citation statements)
references
References 29 publications
17
228
3
20
Order By: Relevance
“…The data of Hulshof et al (1999) indicate that in the United Kingdom, milk and dairy products supply about 40% of all SFA (Table 4), somewhat higher than the data from the National Diet and Nutrition Survey (Henderson et al, 2003). Thus, it may be argued that reducing the intake of SFA would simply be achieved by reducing the consumption of milk and dairy products.…”
Section: Milk and Dairy Products As Sources Of Saturated Fatty Acids mentioning
confidence: 74%
See 1 more Smart Citation
“…The data of Hulshof et al (1999) indicate that in the United Kingdom, milk and dairy products supply about 40% of all SFA (Table 4), somewhat higher than the data from the National Diet and Nutrition Survey (Henderson et al, 2003). Thus, it may be argued that reducing the intake of SFA would simply be achieved by reducing the consumption of milk and dairy products.…”
Section: Milk and Dairy Products As Sources Of Saturated Fatty Acids mentioning
confidence: 74%
“…The TRANSFAIR study (Hulshof et al, 1999) showed that in all the European countries studied, trans isomers of C18:1 were by far the primary TFA in diets. For example, in France and the Netherlands, they represented 54% and 82% of dietary TFA intake by women.…”
Section: Milk and Dairy Products As Sources Of Trans-fatty Acids (Tfa)mentioning
confidence: 99%
“…Intake levels of TFAs found in this study were lower than those reported earlier in Northern America and several European countries. Differences in estimates can, apart from actual differences in intakes, be attributable to differences in food intake data used, differences in analytical methods used for assessing the TFA content and industrial lowering of TFA after the public turmoil on this issue in the past years (Hulshof et al, 1999). Within the TRANSFAIR study, the TFA intake for the separate countries was estimated using data from national food surveys (TRANS-FAIR part 2).…”
Section: Discussionmentioning
confidence: 99%
“…Higher intakes of trans fatty acids (FA) are also associated with increased cardiovascular disease risk (Shingfield et al, 2008). Milk and dairy products are an important source of fat, SFA and trans FA in the human diet (Hulshof et al, 1999), and therefore there is considerable interest in altering milk FA composition to improve long-term human health.…”
Section: Introductionmentioning
confidence: 99%